Delirium related distress experienced by nurses - Baptista,Inês (2023)
Abstract Background: Delirium is described as a distressful experience by patients and their families. Also, among healthcare staff, nurses caring for patients with delirium are the most at risk of high distress related to this syndrome. Aims: To assess nurses’ distress related to delirium and its specific symptoms and severity. To identify factors nurses’ sociodemographic and psychological characteristics and professional experience, that may be associated to this distress. Methods: A prospective study was carried out with nurses caring older adults with delirium in Intensive Care Medicine Service. Distress related to delirium, global psychological distress and burnout in nurses were measured with Delirium Experience Questionnaire, Kessler Psychological Distress Scale and Copenhagen Burnout Inventory, respectively. Results: Eighteen nurses were included (mean age=32 years; 89% women). About 46% of the nurses classified the experience of caring for patients in delirium as moderately distressing. Disorientation and psychomotor agitation were the most distressing symptoms. High distress related to delirium was associated with greater personal (p=0.040) and work-related burnout (p=0.020), and more global psychological distress (p=0.007). Conclusion: Caring for patients with delirium is distressing for nurses, particularly if the disorientation and psychomotor agitation are present and if nurses presented high burnout or psychological distress. This study highlights the need for development of education and support strategies for all professionals dealing with these patients.